Pengaruh Ukuran Perusahaan, Profitabilitas, Dewan Komisaris Independen, Komite Audit Dan Kepemilikan Publik Terhadap Pengungkapan Manajemen Risiko Dengan Komite Manajemen Risiko Sebagai Variabel Moderasi Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Ta - adelia syahfitri; muhammad rizal (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
In this researh, the problem is the tendency of low risk disclosure practices in manufacturing companies in Indonesia. Despite the obligation to submit annual reports, disclosure of risk management is still minimal and often voluntary. The purpose of this research is to analyze the factors that can affect risk management disclosure including company size, profitability, independent board of commissioners, audit committee, public ownership and risk management committee as a moderating variable for risk management disclosure. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022 and research sampling using purposive sampling techniques with specific criteria and therefore the number of samples that match the criteria is 130 companies, with a period of 3 years so that the data totals 390 samples. This research model uses multiple linear regression analysis and moderation regression analysis (MRA). The results showed that company size has a positive effect on risk management disclosure; profitability and audit committee have a negative effect on risk management disclosure; independent board of commissioners and public ownership have no effect on risk management disclosure; risk management committee is able to moderate company size and independent board of commissioners on risk management disclosure; risk management committee is not able to moderate profitability, audit committee and public ownership on risk management disclosure; and company size, profitability, independent board of commissioners, audit committee and public ownership jointly affect risk management disclosure.